2020
DOI: 10.1007/978-3-030-58820-5_32
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on Walkability and its Theoretical Framework. Emerging Perspectives for Research Developments

Abstract: Urbanization identifies the contemporary city as the crucible of human condition. This tendency elicits the issue of the ways in which the built environment affects human behaviour. In particular, walking emerges as a central topic. Walking, in fact, is conceptualized as a vector for engaging with the world, and as a conduit to physical activity, social contact and optional practices. Consequently, a vast body of literature exists, related to the concept of walkability. The latter can be defined as the built e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Pedestrian movements are an important segment of the entire urban mobility and sustainable urban planning and design has to consider walkability of urban spaces as an important issue. The analysis and evaluation of walkability is the subject of numerous works in the literature [1,2]. Different works show evaluations of walkability through specific indicators [1][2][3] also developed through some software tools for the evaluation of walkability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pedestrian movements are an important segment of the entire urban mobility and sustainable urban planning and design has to consider walkability of urban spaces as an important issue. The analysis and evaluation of walkability is the subject of numerous works in the literature [1,2]. Different works show evaluations of walkability through specific indicators [1][2][3] also developed through some software tools for the evaluation of walkability [4].…”
Section: Introductionmentioning
confidence: 99%
“…The indicators in this tool are based on historical data between 1990 and 2010 for the gross population density that reflects the concentration of services and public transit in close proximity, street intersection density as an indicator of street network connectivity, and destination accessibility including access to transportation nodes. The webbased walk scoring is another important tool assessing walkability macroscale indicators usually through quantitative parameters including intersection density, population density, and distance from amenities (Annunziata et al 2020 andGarau et al 2020). Walk scoring is usually utilized in assessing "walking friendless" in the design process of neighborhoods (Sustainable Design Lab 2020).…”
Section: Walkability Microscale and Macroscale Assessment Toolsmentioning
confidence: 99%
“…Moreover, it is evident now that pedestrian-friendly communities have enhanced community connectedness and social capital due to the initiated social interlinked relations and networks among residents (Rogers et al 2013;Masoud 2011;Paranagamage et al 2014;Mazumdar et al 2018). Accordingly, Annunziata et al (2020) and Garau et al (2020) argued that walkability has an ethical significance as it affects people's well-being through positively shaping their physical and social capabilities and also providing them with healthy aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, most of the data and indicators are implemented in urban divisions such as neighborhood units. Annunziata and Garau (2020) investigated walkability based on four concepts: capability, affordance, configuration, and urban ethics. They found that these concepts could be conductive in operationalizing walkability and developing methodological frameworks.…”
mentioning
confidence: 99%